Studies of Nutrition and certain biochemical aspects of the elderly - Abarca Zubieta, Fernando (1954)
In Asylum "San Vicente de Paul" has been studied from the point of clinical and laboratory-dependent alterations of nutrition, as well as certain aspects of lipid metabolism and liver function in 60 individuals. In this paper we present one aspect of this study. Total cholesterol and lipids have a progressive increase in its serum levels, depending on age. The average values ​​for total lipids are of 759 mgs. percent and total cholesterol of 215 milligrams per cent, being noted that this increase is higher in female subjects than in males. The probable mechanism of the disturbances is discussed. It was found that the sedimentation rate of erythrocytes is accelerated, for men an average of 17 mm was found and for women 19, this increase is probably due to qualitative changes of proteins and lipoproteins, the last to increase with age, and it is possible, it is found associated with nutritional deficiencies complex mechanism. The study of the liver function by reacting thymol turbidity shows, according to clinical data, there is no damage of the liver cell. Total protein and serum fractions are within the normal range, according to proper diet protéica wealth. In hemoglobin determinations has confirmed the existence of a moderate degree of anemia, explainable by certain food and partly by age gaps. Mean hemoglobin reached 13.7 gr. %, Ranging from 7.5 to 16.5 gr. %. All subjects tested have oscórbico figures acid in blood plasma significantly below the normal range, in accordance with poor nutritional intake. The average found in the 60 cases is 0.2 mg%, ranging from 0.09 to 0.35 mgs. %. For verification of anthropometric data, we found that the mean values ​​for height and weight are less than those allowed for normal adults in our environment, which is due to own involutive phenomena of aging. It is noted that there is a close relationship between the biochemical results obtained, clinical examination and study of diet. Moreover, housing conditions, health and environment in the Asylum "San Vicente de Paul" are good; as it relates to diet would be appropriate to correct vitamin deficiencies to qualify good regime are subject to the elderly staying in this establishment and are in the care of the Public Welfare of Lima.